If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + -5) = (3x + 6)(x + -3) Reorder the terms: x(-5 + 3x) = (3x + 6)(x + -3) (-5 * x + 3x * x) = (3x + 6)(x + -3) (-5x + 3x2) = (3x + 6)(x + -3) Reorder the terms: -5x + 3x2 = (6 + 3x)(x + -3) Reorder the terms: -5x + 3x2 = (6 + 3x)(-3 + x) Multiply (6 + 3x) * (-3 + x) -5x + 3x2 = (6(-3 + x) + 3x * (-3 + x)) -5x + 3x2 = ((-3 * 6 + x * 6) + 3x * (-3 + x)) -5x + 3x2 = ((-18 + 6x) + 3x * (-3 + x)) -5x + 3x2 = (-18 + 6x + (-3 * 3x + x * 3x)) -5x + 3x2 = (-18 + 6x + (-9x + 3x2)) Combine like terms: 6x + -9x = -3x -5x + 3x2 = (-18 + -3x + 3x2) Add '-3x2' to each side of the equation. -5x + 3x2 + -3x2 = -18 + -3x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -5x + 0 = -18 + -3x + 3x2 + -3x2 -5x = -18 + -3x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -5x = -18 + -3x + 0 -5x = -18 + -3x Solving -5x = -18 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -5x + 3x = -18 + -3x + 3x Combine like terms: -5x + 3x = -2x -2x = -18 + -3x + 3x Combine like terms: -3x + 3x = 0 -2x = -18 + 0 -2x = -18 Divide each side by '-2'. x = 9 Simplifying x = 9
| 6(x-8)=12(x+4) | | 3n+5n+2+n= | | (4q+9)(4q+9)=0 | | 4(x+3)=2x+10+2x | | 46/63-5/7 | | 57+57+123+x=360 | | 5+3(y-4)=5(y+3)-y | | -9+6-12= | | 5+7g=54 | | 12x+17x-6+5=-5x+5-6 | | 63=9(2-w) | | 6-4(5p+9)+3(2+p)=-18 | | 3t-18=4(-3-3/4) | | -6x+5(1)=1 | | 6n=64 | | 4.6x-14.6=5.4 | | 2(n+n+1)=(n+2)-36 | | 3/5x-2=1/5 | | 10y(y+2)+3x=5(3-x) | | 4y-2(x-y)= | | 5x-3x+16=-x+8 | | 9w-8=64 | | 5.50-3.75= | | 8+2x+3-x=2+1 | | (3/x)-2=11 | | J-62/4=5 | | -6x+-9=1 | | 4s-10=6 | | 8k-5= | | 6(w-1)=2w+4-2(-4w-2) | | -4n+7=1 | | 35=4y+y |